Teachers’ Strategies to Teach English for Young Learners with Special Needs in Inclusive School - Salsabila Bazighoh Zahron; Hepy Adityarini; Agus Wijayanto (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Most schools in Indonesia do not consider English to be a compulsory subject. English is considered local content and an additional subject, especially in elementary schools. However, even though English is not the main subject, the English subject has a strategic role in preparing students from an early age to face global association. This study aims to analyze the strategiesteachers apply to young learners with special needs in introducing and teaching English to them. This study employed the case study qualitative research design. In this study, the researcherscollected data using interviews and observation guides. The research subjects in this study were three teachers, three parents, a headmaster and an inclusion coordinator. This study found that teachers’ teaching strategies vary depending on the conditions of young learners with special needs. This research implies thataccompanying teachers for young learners with special needs become more aware of the importance of teaching strategies adapted to students’ abilities. Apart from that, teachers also get new ideas in implementing various teaching strategies.